The relationship between the crime of wrongdoing and the crimes of danger and harm - M . Dr. Sami Meddeb Mohammed Al-Obaidi (The college of law and political science journal, 2023)
Wen researching the issue of the relationship of the crime of error with the crimes of harm and danger, we see that jurisprudence divided the error into two types: conscious error and unconscious error.      Its occurrence, he commits his behavior and achieves the damage he expected.       As for the second type (unconscious error), this type of error is based on negative expectation, which is available by the will of the behavior that results in an unlawful results, represented by a certain harm that the perpetrator did not expect and could have anticipated and avoided.     There are two theories that have crystallized the specific criterion  for anticipating harm , namely the personal theory and the objective theory , and jurisprudence has seen that the objective theory is preferable to others in dealing with this issue